Significance of umbilical artery Doppler velocimetry in the perinatal outcome of the growth restricted fetuses - Anshul, Deshmukh (Springer-Verlag, 2010)
OBJECTIVES: To evaluate the role of umbilical artery Doppler in growth restricted fetuses. METHODS: In a prospective observational study, 100 pregnant women with growth restricted fetuses confirmed by ultrasound were evaluated by umbilical artery Doppler velocimetry after 28 weeks of gestation. Outcome of the pregnancy was recorded for the normal Doppler group (n=54) and abnormal Doppler group (n=46). Abnormal Doppler group consisted of low end diastolic flow group (n=29) and absent or reversed end diastolic flow (REDF) group (n=17). RESULTS: Fetuses with abnormal umbilical flow velocimetry had higher incidence of oligohydramnios and abnormal NST compared to the fetuses with normal umbilical flow. The average birth weight and gestational age at delivery were lower in the abnormal Doppler group. Neonates with abnormal umbilical artery velocimetry had increased incidence of caesarean delivery, low apgar scores at birth, increased NICU admissions, increased requirement of positive pressure ventilation, and higher perinatal morbidity and mortality. CONCLUSION: Umbilical artery Doppler velocimetry should be used in the management of the intrauterine growth restricted fetuses, as it helps in differentiating fetus with pathological growth restriction at risk for perinatal complications from small and healthy fetuses.